Determination of Tobramycin in M9 Medium by LC-MS/MS: Signal Enhancement by Trichloroacetic Acid. (26th April 2018) - Huang, Liusheng; Haagensen, Janus Anders Juul; Verotta, Davide; Cheah, Vincent; Spormann, Alfred M.; Aweeka, Francesca; Yang, Katherine
Abstract : It is well known that ion-pairing reagents cause ion suppression in LC-MS/MS methods. Here, we report that trichloroacetic acid increases the MS signal of tobramycin. To support studies of an in vitro pharmacokinetic/pharmacodynamic simulator for bacterial biofilms, an LC-MS/MS method for determination of tobramycin in M9 media was developed. Aliquots of 25 μ L M9 media samples were mixed with the internal standard (IS) tobramycin-d5 (5 µ g/mL, 25 µ L) and 200 µ L 2.5% trichloroacetic acid. The mixture (5 µ L) was directly injected onto a PFP column (2.0 × 50 mm, 3 µ m) eluted with water containing 20 mM ammonium formate and 0.14% trifluoroacetic acid and acetonitrile containing 0.1% trifluoroacetic acid in a gradient mode. ESI + and MRM with ion m / z 468 → 324 for tobramycin and m / z 473 → 327 for the IS were used for quantification. The calibration curve concentration range was 50–25000 ng/mL. Matrix effect from M9 media was not significant when compared with injection solvents, but signal enhancement by trichloroacetic acid was significant (∼3 fold). The method is simple, fast, and reliable. Using the method, the in vitro PK/PD model was tested with one bolus dose of tobramycin.